Individual and institutional influences on EU labour market returns to education: a comparison of the effect of the 2008 economic crisis on eight EU countries. Issue 2 (14th March 2020) - Robert, Peter; Saar, Ellu; Kazjulja, Margarita
ABSTRACT: This paper explores cross-national variations in the impact of education on labour market outcomes using the risk of unemployment and occupational status as the key dependent variables. The study applies a comparative perspective on eight EU countries (three from CEE), representing different relationships between the education system and the labour market with various degrees of inequality, welfare provisions and labour market flexibility. A temporal comparison investigates the influence of the 2008 economic crisis. The study employs data from the European Union Labour Force Survey 2007, 2009 and 2014. Binary and ordinary least squares regressions are the main analytical methods. Models are fitted to the pooled data and interactions are applied to elaborate on country and temporal variations. The analysis reveals the persistence of returns to school investments; the crisis exerts bigger risk and loss for the less educated. However, this impact is markedly shadowed by the institutional variation at the country level. High flexibility and low inequality could provide some defence, while corporatist features and employment protection decreased the crisis effects. Post-communist countries were hit harder but with a characteristic variance: Slovenia was less affected, Estonia recovered the crisis faster and Hungary was affected at most.